1993
DOI: 10.1080/10862969309547828
|View full text |Cite
|
Sign up to set email alerts
|

Story Map Instruction Using Children's Literature: Effects on First Graders' Comprehension of Central Narrative Elements

Abstract: This study investigated the effectiveness of instruction in story mapping as a means to promote first-grade students' comprehension of central story elements in children's literature. Participants were 74 children in four first-grade classrooms, which were randomly assigned to one of four groups: (a) a Story Mapping 1 (SM1) group, in which students were taught to construct story maps for unadapted, unabridged children's stories they had read; (b) a Story Mapping 2 (SM2) group, which involved the same instructi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
1
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(54 citation statements)
references
References 25 publications
3
45
1
5
Order By: Relevance
“…The process we teach is one in which children learn the structure of stories and practice applying this knowledge to new texts. Previous research has shown that story structure instruction improves readers' memory and comprehension for stories (e.g., Baumann & Bergeron, 1993;Garner & Bochna, 2004), and we extend this literature by studying the effects of text structure instruction for very young elementary grade and special education students. By testing the effects of this instruction as children are engaged in a listening, rather than reading, comprehension activity, we address the need for instructional methods that target the comprehension processes of children who cannot yet fluently decode text.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…The process we teach is one in which children learn the structure of stories and practice applying this knowledge to new texts. Previous research has shown that story structure instruction improves readers' memory and comprehension for stories (e.g., Baumann & Bergeron, 1993;Garner & Bochna, 2004), and we extend this literature by studying the effects of text structure instruction for very young elementary grade and special education students. By testing the effects of this instruction as children are engaged in a listening, rather than reading, comprehension activity, we address the need for instructional methods that target the comprehension processes of children who cannot yet fluently decode text.…”
Section: Introductionmentioning
confidence: 89%
“…Baumann and Bergeron (1993), for example, used a story mapping technique to successfully teach children a story structure strategy. Garner and Bochna (2004) taught children to use a story structure strategy during listening comprehension tasks.…”
Section: Story Structure Knowledgementioning
confidence: 99%
“…Stahl (2004) reported that four instructional practices which were widely used by primary grade teachers had been supported by research results. These include, for example, story map (Baumann and Bergeron, 1993), question and answer (Raphael and Wonnacott, 1985), reciprocal teaching (Palinscar and Brown, 1984), and teacher-generated questioning (Taylor et al, 2000). Shanahan et al (2010) identified six reading strategies that have evidence of improving primary grade students' reading skills from Kindergarten through 3rd Grade.…”
Section: Reading Comprehension Instructional Practices In the Primarymentioning
confidence: 99%
“…The structural elements (story grammar) common to most narrative texts include, for example, the setting, characters, goal, problem, plot or action, resolution, and a theme (Baumann & Bergeron, 1993;Morrow, 1996;and Pressley et al, 1990). Given that students with LD do not have as well developed a sense of story grammar as their nondisabled peers and often have trouble recalling elements of a story, particularly the more abstract elements such as theme and resolution, several interventions have focused on teaching story grammar to improve their reading comprehension.…”
Section: Narrative Textsmentioning
confidence: 99%